2022
DOI: 10.1001/jamadermatol.2022.0351
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Prevalence and Incidence of Pediatric Alopecia Areata Using Electronic Health Record Data

Abstract: OBJECTIVE To determine the prevalence and incidence of AA in a pediatric population across time, age, sex, race and ethnicity, and geographic areas within the US. DESIGN, SETTING, AND PARTICIPANTSIn this multicenter cohort study conducted among 5 children's hospitals, data (January 2009 to November 2020) were collected from a standardized electronic health record (PEDSnet database, version 4.0) to evaluate the incidence and prevalence of pediatric AA. The study cohort included patients younger than 18 years wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
0
16
1
1
Order By: Relevance
“…Compared with our results among children and adolescents, similar temporal and subgroup trends were observed in a recent US hospital-based study using electronic health records data. This latter study found that AA prevalence among pediatric patients (mean age, 9 years) had doubled during the last decade (overall prevalence of 0.11% from 2009-2020), which was consistent with the slight increase in AA rates over time in the present study. Also consistent with the present study, pediatric AA IRs were higher among children who were older and female; in addition, the latter study identified Asian and Hispanic children as high-risk subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with our results among children and adolescents, similar temporal and subgroup trends were observed in a recent US hospital-based study using electronic health records data. This latter study found that AA prevalence among pediatric patients (mean age, 9 years) had doubled during the last decade (overall prevalence of 0.11% from 2009-2020), which was consistent with the slight increase in AA rates over time in the present study. Also consistent with the present study, pediatric AA IRs were higher among children who were older and female; in addition, the latter study identified Asian and Hispanic children as high-risk subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…The annual AA PRs among children aged 6 to 11 years in the present study (0.12%- 0.14%) were higher than the rates in this hospital-based study (0.04%-0.08%); IRs were also higher in the present study. 35…”
Section: Children and Adolescentsmentioning
confidence: 99%
“…A recent North American study found a 0.11% prevalence rate of paediatric AA, with significantly higher incidence in Asian, Black and Hispanic children. 1 AA of the scalp can present in diverse shapes and to various extent, from a single round patch to complete hair loss termed as alopecia totalis. One of the most common comorbidities of AA is atopic dermatitis (AD).…”
Section: Introductionmentioning
confidence: 99%
“…AA is a common, non-scarring type of hair loss, affecting approximately 1.7% of the population [1,12,13,14]. In a study of 200 patients from Kashmir, sex incidence was reported for males to females as 3 to 1 respectively [15].…”
Section: Discussionmentioning
confidence: 99%